Hubungan Cakupan Tablet Fe3 dengan BBLBR di Provinsi Jawa Timur tahun 2017 - Irohatul A'ila; Sri Sumarmi (Amerta Nutrition, 2019)
Background: Low birth weight (LBW) is one of the children's health indicators. Based on the health profile of East Java province in 2017, the prevalence of LBW increased from 3.6% in 2016 to 3.8%. Besides increasing the prevalence of LBW, there was a decrease in Fe3 tablet coverage. In 2016 Fe3 tablets decreased by 88.2% and decreased in 2017 to 87.4%. A decrease in Fe3 tablet coverage is likely to cause a high prevalence of LBW.Objective: This study aimed to know the relationship of Fe3 tablets with the prevalence of LBW in East Java province in 2017. Methods: The type of this research was quantitative research using secondary data on the health profile of East Java province in 2017. The observed variables was Fe3 tablet coverage and LBW prevalence. Data analysis using a Pearson correlation and Chi-square test.Result: The regency/city included in the category of low Fe3 tablet coverage was 55.3% and as many as 21.1% regency/city with LBW prevalence were included in the category of not public health problems. Pearson correlation test results (p-value=0.270) and Chi-square test (p-value=0.206) showed there was no relationship between the coverage of Fe3 tablets with prevalence of LBW in East Java Province in 2017.Conclusion: The regency/city that has low Fe3 tablet coverage doesn’t necessarily have a high LBW prevalence. Further research is needed to find out other factors related to the high prevalence of LBW in East Java Province in 2017.ABSTRAKLatar Belakang: Berat badan lahir rendah (BBLR) merupakan salah satu indikator kesehatan anak. Berdasar profil kesehatan Provinsi Jawa Timur tahun 2017, kejadian BBLR mengalami peningkatan dari 3,6% pada tahun 2016 menjadi 3,8%. Selain peningkatan prevalensi BBLR, terjadi penurunan cakupan tablet Fe3 (90 tablet Fe) yang diberikan kepada ibu hamil. Pada tahun 2016 cakupan tablet Fe3 sebesar 88,2% dan menurun pada tahun 2017 menjadi 87,4%. Cakupan pemberian tablet Fe kepada ibu hamil merupakan salah satu faktor yang dapat berhubungan dengan kejadian BBLR.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan cakupan tablet Fe3 untuk ibu hamil dengan kejadian BBLR di Provinsi Jawa Timur pada tahun 2017.Metode: Jenis Penelitian ini adalah penelitian kuantitatif menggunakan data sekunder profil kesehatan Provinsi Jawa Timur tahun 2017. Data sekunder yang digunakan berupa data cakupan tablet Fe3 dan kejadian BBLR. Analisis data menggunakan uji korelasi perason.Hasil: Hasil uji korelasi pearson antara cakupan tablet Fe3 dengan kejadian BBLR di Provinsi Jawa Timur pada tahun 2017 menunjukkan nilai p-value <0,05 (p=0,000). Hal ini menunjukkan adanya hubungan antara cakupan tablet Fe3 dengan kejadian BBLR di Provinsi Jawa Timur tahun 2017 dengan koefisiensi korelasi r=0,706.Kesimpulan: erdapat hubungan antara cakupan tablet Fe3 dengan kejadian BBLR di Provinsi Jawa Timur pada tahun 2017.